PENGARUH LINGKUNGAN KERJA, STRES KERJA DAN MOTIVASI TERHADAP KINERJA PETUGAS KEBERSIHAN PADA DINAS LINGKUNGAN HIDUP KABUPATEN DAIRI - Imelda Siburian; Meriaty Simanullang; Eva Julianti Lubis; Setiono .; Morina Annelita (Universitas Islam Islam Sumatera Utara, 2020)
The problems is influence influence between work environment, work stress and motivation on the performance of janitors at the Dinas Lingkungan Hidup Kabupaten Dairi. Where proposed three independent variables and one independent variable, namely the work environment (X1), work stress (X2) and motivation (X3) and performance (Y1) as the dependent variable. This study aims to determine whether there is an influence between work environment, work stress and motivation on the performance of janitors at the Dinas Lingkungan Hidup Kabupaten Dairi. The study was a quantitative study using survey methods. Subjects were study were janitors at the Dinas Lingkungan Hidup Kabupaten Dairi with 100 respondents. Validity and Reliability is performed to see validity of the study questionnaire was valid or not. T test performed to determine whether the independent variable partially has a significant influence on the dependent variable and the F test is performed to determine whether the independent variable simultaneously has a significant influence on the dependent variable. The results showed : (1) Work environment variables had a positive and significant effect on the performance of janitors at the Dinas Lingkungan Hidup Kabupaten Dairi by 0.506 or 50.60%, (2) Work stress variables had a positive but not significant effect on the performance of janitors at the Dinas Lingkungan Hidup Kabupaten Dairi by 0.169 or 16.90%, (3) the variable of work motivation has a positive and significant effect on the performance of janitors at the Dinas Lingkungan Hidup Kabupaten Dairi by 0.364 or 36.40% and (4) the variable of work environment, work stress and work motivation have a positive and significant effect on performance janitors at the Dinas Lingkungan Hidup Kabupaten Dairi by 60.90%, while the remaining 39.10% is influenced by other factors not examined